The future of clinical pharmacology in the NHS. Issue 2 (19th February 2021) - Walker, Lauren; Bennett, Frances; Scourfield, Andrew; Payne, Rupert
Abstract : Clinical pharmacologists are well placed to address the growing challenges of multimorbidity and polypharmacy through their expertise in medicines optimisation and experience working at the interface between primary and secondary care. However, the speciality needs to improve its visibility in order to highlight the clinical and economical value it can bring to the NHS.